ANALISIS YURIDIS PERJANJIAN PRANIKAH DI INDONESIA DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA - Dae Panie, Norci P; Jacob, Yossie M Y; Pello, Helsina F (Petitum Law Journal, 2025)
This study analyzes the legal protection and implications of prenuptial agreements as regulated under the Indonesian Civil Code. Prenuptial agreements, which are created prior to marriage, serve as legal instruments that govern the division, management, and ownership of property between future spouses. Although their legal standing is acknowledged, the practical application of these agreements in Indonesia remains limited due to cultural stigma, insufficient public awareness, and the perception that such agreements contradict traditional values. This normative juridical research employs a statutory and analytical approach to examine relevant legal provisions, especially those found in the Civil Code, Law Number 1 of 1974 on Marriage, and the Compilation of Islamic Law. The findings indicate that while existing legal instruments provide a basis for regulating property relations through prenuptial agreements, they lack a comprehensive framework for addressing broader aspects such as economic rights, child protection, and spousal responsibilities. Moreover, there is an urgent need to reform and harmonize related regulations to enhance legal certainty and prevent future disputes. Strengthening legal literacy and promoting the social legitimacy of prenuptial agreements are also essential steps to ensure that these agreements function not only as protective legal tools but also as preventive mechanisms that contribute to household stability and justice in marriage.